Xanthophyllum longum - Tanggaraju, S.; Hor, C.S.; Sugau, J.; Nilus, R.; Colin Ruzelion Maycock; Matusin, Dg Ku Rozianah, M.; Khoo, E.; Damit, A.; Mohd Yusof, Nur Adillah, M.Y.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Xanthophyllum longum is only known from Sg Pinangah Forest Reserve (commercial forest reserve) in Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 4 km2 the species has experienced a reduction of AOO (67%) and EOO (over 90%). Although the species is not on the harvested timber list and reduced impact logging protocol is being practiced within the forest reserve, the decline of habitat quality is still plausible, hence the species is assessed as Critically Endangered. Xanthophyllum longum is endemic to Sabah, Malaysia. Based on herbarium record it is confined to Sg Pinangah Forest Reserve. Due to urbanization and past historical events the species has experienced reduction of in area of occupancy (AOO) of 67% and extent of occurrence (EOO) of over 90%, resulting in the current AOO and EOO for the species to be 4 km2 respectively.